Proyecto de factibilidad para la producción y comercialización de té a base de la planta de buscapina (Parietaria officinalis) en la ciudad de Loja. - Gaona Vicente, Lizbeth Yajaira (2024)
This research paper entitled “Feasibility Project for the Production and Commercialization of Tea Based on the Buscapina Plant (Parietaria officinalis) in the City of Loja” was conducted with the objective of evaluating the viability of industrializing this new product. Its implementation aims to address consumer needs by providing a natural and healthful alternative, while concurrently anticipating a positive economic impact through its commercialization. To ascertain the feasibility of the project, comprehensive studies were undertaken, encompassing: market, technical, economic, and financial analyses. The methodology employed was exploratory-descriptive, utilizing a mixed approach (qualitative and quantitative non-experimental). The methods applied included inductive, deductive, statistical, analytical, and mathematical. Additionally, techniques with data collection methods such as surveys, interviews and literature reviews were used. The financial outcomes indicate that the project is feasible, evidenced by a positive Net Present Value (NPV) of $60 158.22; an Internal Rate of Return (IRR) of 29.84% which exceeds the opportunity cost; a Capital Recovery Period (PRC) is estimated at 2 years and 6 months; and a Benefit-Cost Ratio (RBC) reflecting a return of $0.41 for every dollar invested. Lastly, the sensitivity analysis (SA) demonstrates that the project can endure a cost increase of 14.59% and a revenue decrease of 10.35%.